PENGARUH DISIPLIN DAN MOTIVASI TERHADAP KINERJA PEGAWAI (Studi Pada Kantor Camat Brang Ene Kabupaten Sumbawa Barat) - I Ismawati; Winda Kurniasih; Subhan Purwadinata (Fakultas Ekonomi dan Manajemen, 2022)
The purpose of this study was to determine the effect of discipline and work motivation on the performance of employees in the Brang Ene District Office, West Sumbawa Regency. This type of research is associative. The data used is quantitative data in the form of respondents' responses in answering questions given through questionnaires regarding compensation and work productivity of employees who are scored (scoring). Data were obtained from primary sources, namely from the results of questionnaires distributed to research respondents, namely all employees of the Brang Ene sub-district office, totaling 26 people. Data were analyzed using simple linear regression analysis techniques, individual parameter hypothesis testing (t test), simultaneous parameter hypothesis testing (F test), and determinant coefficient test (R2). The results of this study indicate that discipline and work motivation have a positive and significant effect on employee performance at the Brang Ene District Office, West Sumbawa Regency, both partially and simultaneously. The degree of influence of work discipline and work motivation on employee performance at the Brang Ene sub-district office of West Sumbawa Regency is 60.4%, while the remaining 39.6% is influenced by other variables outside this research model.